PENGARUH KEPEMIMPINAN, PENGEMBANGAN SUMBER DAYA MANUSIA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL (Survei pada Pegawai Negeri Sipil Kantor Dinas Pendidikan Kota Surakarta) - Rahayu Triastity, Dina Wijayanti Whardhaya, Suprayitno & (Universitas Slamet Riyadi, 2018)
This study aims to determine the influence of leadership, human resourcedevelopment and work discipline on the performance of civil servants. Types of data used in this study are Qualitative Data and Quantitative Data. Sources of data used in this study were obtained from survey results and primary data of the Education Office of Surakarta City. The population in this research is 74 civil servants. Data analysis techniques used classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination. The result of the research shows that leadership has positive and significant influence to civil servant performance, human resource development has negative effect on civil servant performance, work discipline has negative effect on civil servant performance and leadership has dominant influence to civil servant performance compared to with the development of human resources and work discipline.Keywords: leadership, human resource development, work discipline, employeeperformance